Efektivitas Model Core dalam Pembelajaran Menulis Teks Biografi dalam Pembelajaran Bahasa Indonesia Kelas X di SMK - Tamara Geraldin; Agnes Apryliana; Sigit Andi Prasetya Dinata (Universitas Palangka Raya, 2024)
Knowing the effectiveness of the CORE model in learning to write Indonesian biographical texts for class X Karangpucung Darussalam Vocational School is the aim of this research. The type used in this research is quantitative with a quasi-experimental design. The sampling technique is random sampling technique. Class X TKR 1 as the experimental class and class X TBSM 1 as the control class. In this analysis the data collection method is the experimental method. The results of the t-test assume that if t_count > t_table is 5.312 > 2.021 and the significance value is 0.05 then H_a will be accepted. The purpose of these results is to conclude that there is a significant difference between the post-test performance data for the experimental class and the control class. Therefore, this model has proven to be effective in writing biographical texts in class X at Karangpucung Darussalam Vocational School.